2021
DOI: 10.1128/spectrum.00996-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sample Pooling for SARS-CoV-2 Detection in Nasopharyngeal Swab and Saliva Samples with the Idylla SARS-CoV-2 Test

Abstract: To control outbreaks of coronavirus disease 2019 (COVID-19) and to avoid reagent shortages, testing strategies must be adapted and maintained for the foreseeable future. We analyzed the feasibility of pooling NPS and saliva samples for SARS-CoV-2 testing with the Idylla SARS-CoV-2 test, and we found that sensitivity was dependent on the pool size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, when outbreaks occur locally and spread quickly, gene sequencing will not meet the needs of large-scale rapid screening. Presently, several countries and regions have carried out mixed testing of unknown SARS-CoV-2 samples to achieve the goal of rapid screening of positive cases ( Bogere et al, 2021 ; Heaney et al, 2021 ; Hofman et al, 2021 ), which requires a higher sensitivity of testing methods. Our experiments showed that the PCR-CRISPR method could detect 0.1% of target nucleic acids in mixed samples ( Wen et al, 2021 ), providing new insights for large-scale rapid screening of variants ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when outbreaks occur locally and spread quickly, gene sequencing will not meet the needs of large-scale rapid screening. Presently, several countries and regions have carried out mixed testing of unknown SARS-CoV-2 samples to achieve the goal of rapid screening of positive cases ( Bogere et al, 2021 ; Heaney et al, 2021 ; Hofman et al, 2021 ), which requires a higher sensitivity of testing methods. Our experiments showed that the PCR-CRISPR method could detect 0.1% of target nucleic acids in mixed samples ( Wen et al, 2021 ), providing new insights for large-scale rapid screening of variants ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%